Genetic influence on the working memory circuitry: Behavior, structure, function and extensions to illness - Karlsgodt, K; Bachman, P; Winkler, A; Bearden, C; Glahn, D (Elsevier, 2011)
Working memory is a highly heritable complex cognitive trait that is critical for a number of higher-level functions. However, the neural substrates of this behavioral phenotype are intricate and it is unknown through what precise biological mechanism variation in working memory is transmitted. In this review we explore different functional and structural components of the working memory circuitry, and the degree to which each of them is contributed to by genetic factors. Specifically, we consider dopaminergic function, glutamatergic function, white matter integrity and gray matter structure all of which provide potential mechanisms for the inheritance of working memory deficits. In addition to discussing the overall heritability of these measures we also address specific genes that may play a role. Each of these heritable components has the potential to uniquely contribute to the working memory deficits observed in genetic disorders, including 22q deletion syndrome, fragile X syndrome, phenylketonuria (PKU), and schizophrenia. By observing the individual contributions of disruptions in different components of the working memory circuitry to behavioral performance, we highlight the concept that there may be many routes to a working memory deficit; even though the same cognitive measure may be a valid endophenotype across different disorders, the underlying cause of, and treatment for, the deficit may differ. This has implications for our understanding of the transmission of working memory deficits in both healthy and disordered populations.